The Problem of Election Administration Professionalization in Modern Public Administration in Ukraine - Valentyn Orlov (Соціологічні студії, 2018)
The crisis of confidence in the authorities in Ukraine is largely caused by the lack of public confidence in the bodies performing public functions. Especially, it true electoral process, which accumulates problem of political choice and legitimacy. In most cases, disbelief voters in the election results and fair ballot election commissions generated unprofessional. Since the elections in Ukraine have become permanent phenomenon, there is a contradiction between the powerful nature of the powers that perform election commissions and lack of professionalism of the members of these commissions, which would facilitate the strict observance of election procedures and rules. This institutional problem of the current political spheres of society leads to negative trends in political life. Meanwhile, elections at all levels make the experience of Ukrainian citizens to participate in elections to seek earnings during election campaigns. Commercialization of the election process creates a phenomenon where political power delegated to the electoral commissions as collegiate bodies performing public functions to legitimize power, not professionals, and politically loyal mercenaries, for which important earnings of compliance with election law. The solution is seen by us in the widest possible professionalization of election commissions of all levels. This will improve the system of election administration, increase public confidence in the election results and eliminate the tendency to commercialize the process.